Areas of endemism for Anablepidae (Teleostei: Cyprinodontiformes): A monophyletic family of freshwater fishes in the Neotropics - Frota, Augusto; Pavanelli, Carla Simone; Da Graça, Weferson Júnio (Zootaxa, 2019)
Knowledge on the hydrological evolution of the Neotropical region was used along with the current distribution of the anablepid species to investigate the historical biogeography of this family. Areas of endemism were delimited by endemicity analysis resulting in seven individual areas of endemism and three consensus areas located in northwestern Argentina, southern Brazil, and northern South America. These areas were discussed in the context of anablepid species diversification, especially for the genus Anableps and the subgenera Jenynsia and Plesiojenynsia. The existence of areas of endemism for the family analyzed reveals an intimate association with historical events that occurred in the geological evolution of South America, which can be associated with the main diversification patterns and historical hypotheses in the context of Neotropical freshwater fishes biogeography.